Cover Picture: Catalytic Enantioselective Intermolecular Desymmetrization of 3‐Substituted Oxetanes (Angew. Chem. Int. Ed. 26/2013). Issue 26 (5th June 2013) - Wang, Zhaobin; Chen, Zhilong; Sun, Jianwei
<x xml:space="preserve">Abstract</x> Different chiral building blocks can be obtained through an enantioselective ring‐opening reaction of prochiral 3‐substituted oxetanes, as described by J. Sun and co‐workers in their Communication on page 6685 ff. The proper choice of the chiral phosphoric acid catalyst and the nucleophile resembles the right choice of a good cook and the raw materials required for a variety of delicious meals.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>